Influences of preheating parameters on the quality of weld by thermite rail welding - Romadorn Burapa; Hein Zaw Oo; Wissarut Sangwiman; Prapas Muangjunburee (Materials Research Express, 2024)
The major goal of this study is to enhance the mechanical and metallurgical characteristics of rail steel grade R260 joined by thermite welding under various preheating conditions, including preheating time and gas pressure. Mainly two conditions, referred to as the Normal Condition and Improved Condition, are carried out for experiments. Prior to welding, the Normal Condition was preheated using liquefied petroleum gas (LPG) and oxygen gas pressures of 1 bar and 4.5 bar for 3 min, and the Improved Condition was preheated using liquefied petroleum gas and oxygen gas pressures of 1.2 bar and 4.5 bar for 6 min and 30 s. To investigate the mechanical and physical properties, micro-Vickers hardness tests, tensile tests and slow bending tests were also carried out. Welded metal in Normal Condition has many defects, including gas holes and shrinkage cavities. When comparing the Normal Condition to the Improved Condition, the Improved Condition demonstrates significantly more bending load and deflection. Specifically, the thermite welded rail sample of Improved Condition demonstrated a remarkable ability to endure bending loads of 108 tonnes and a deflection of 16 mm, and this sample remained unbroken until it exceeded 50% of the standardized deflection limit (10 mm). In addition, the average hardness values for the Improved Condition of the weld metal zone and the heat-affected zone were 331 HV and 289 HV, respectively. The Normal Condition produced an unsatisfactory fracture surface after slow bending test. This was caused by weld defects at the thermite weld due to inappropriate preheating.